2016
DOI: 10.1186/s40689-016-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing and fastness properties of Quercus robur with natural mordants on natural fibre

Abstract: Dyeing potential of a natural dye extracted from Quercus robur L. (fruit cups) with a combination of Salix alba L. and Populus deltoides Bartram ex marsh (wood ash) mordants was studied on wool, cotton, silk and pashmina fabrics. Experiment was carried out in different combinations including and excluding mordants by adopting different mordanting methods. Dyeing performance was assessed in terms of dye absorption (%), Colour values (CIELAB), Colour strength (K/S), and fastness properties. The dye in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…1a) is darker than the clothes mordanted by alum (Fig 1b). The positive b* value indicates tendency to form bright yellowish tone, while the negative refers to blue colour [14], [15]. High value of ∆b* therefore, indicates a yellow colour, and visually this is in line to the result presented in Fig.…”
Section: Colours Of Block-printed Batik By the Application Of Differesupporting
confidence: 78%
See 1 more Smart Citation
“…1a) is darker than the clothes mordanted by alum (Fig 1b). The positive b* value indicates tendency to form bright yellowish tone, while the negative refers to blue colour [14], [15]. High value of ∆b* therefore, indicates a yellow colour, and visually this is in line to the result presented in Fig.…”
Section: Colours Of Block-printed Batik By the Application Of Differesupporting
confidence: 78%
“…The wax, natural dyes, and water attached or absorbed by each clothes were also measured according to our previous research [13]. Colour measurement of the Myrobalan extract and the coloured clothes were conducted using a Minolta CR-200 chromameter resulting the L*, a*, and b* parameters which were used to calculate the total colour change (∆E) [14], [15].…”
Section: Methodsmentioning
confidence: 99%
“…Production technologies of natural colorants from plants could vary from simple solvent extraction to sophisticated techniques depends on the product requirement and its purity. The extraction procedure such as soxhlet method to obtained colour from Quercus robur L. 60 , supercritical fluid extraction and pressurized liquid extraction on annatto seeds and jabuticaba skins 61 , and microwave assisted extraction used on milkweed leaves to get its colour 62 are among several techniques commonly applied. After the extraction process, purification and drying are essential to ensure the quality of the finished product.…”
Section: Production Technologies Of Natural Colorantmentioning
confidence: 99%
“…Many researchers showed that various natural‐based materials develop color in combination with inorganic mordants, namely, Fe, Cu, Zi, and Al. The mordants help the dyes to fix well and then prevent the color from fading due to exposure to light and washing out . In view of these issues, persisting with natural alternative materials for dyeing, this study attempted the use of plant constituents from mekmeko for coloring of leather.…”
Section: Introductionmentioning
confidence: 99%
“…The mordants help the dyes to fix well and then prevent the color from fading due to exposure to light and washing out. [19][20][21] In view of these issues, persisting with natural alternative materials for dyeing, this study attempted the use of plant constituents from mekmeko for coloring of leather.…”
Section: Introductionmentioning
confidence: 99%